ON APPROXIMATION OF THE SOLUTIONS OF BOUNDARY-VALUE PROBLEMS IN UNBOUNDED DOMAINS - Dallakyan, G. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
In this paper, it is proved that the solution of the boundary value problem in an unbounded domain Ω can be obtained as the limit as r → ∞ of the solution ur of the boundary value problem in a bounded domain Ω Ω B_ r, μ, where B_ r, μ={x; |x |_μ < r} is a generalized ball. A similar result is obtained for solutions of problems in a half-space.